O requisito da sustentabilidade nas universidades públicas brasileiras à luz da análise crítica do discurso - Onuma, Fernanda Mitsue Soares (2017)
The advance of neoliberalism has favored the de-accountability of the State in investments in areas essential to population wellbeing, such as health, education and culture, in detriment of fiscal adjustment policies that benefit agents from the financial market. In this context, in which Brazil has achieved a prominent position since the 1990’s with the so-called State Managerial Reform, Brazilian higher public education comes to adopt managerialist ideological discourses, characterized by the discursive colonization of Public Administration by the entrepreneurial discourses (CUNHA, 1993; 2007c; HARVEY, 2014; RODRIGUES, 2010). In light of this panorama, we seek to understand, by means of the Critical Discourse Analysis (CDA) in Fairclough (1985; 1992; 2001; 2005; 2008; 2010; 2012), the process of organizational change by which sustainability has become a requisite for Brazilian public universities. The concept of sustainability has been appropriated in organizations under different perspectives, depending on the group that uses it, from radical environmentalists, governments and non-governmental organizations, and, even by companies, which have distorted its sense in order to stimulate its businesses (BARBIERI, 2012; DIAS; TEODÓSIO, 2011; TEODÓSIO; BARBIERI; CSILLAG, 2006). Thus, despite involving more than the use of technologies and environmentally correct management practices, its use in Brazilian public organizations have been limited to eco-efficiency or to the reduction of consumption of resources such as water and electric energy (BARBIERI, 2012; DIAS; TEODÓSIO, 2011; FREITAS, 2011; NASCIMENTO, 2012). By means of the text ACD produced by MEC and by a Brazilian public university pointed as coauthor of this decree, we identified that the discourse on sustainability emerged from this university for the economy of financial resources in face of the context of cuts in the budgets of higher education in the country. We identified that these point to the use of discourse strategies as lexical choices, the use of discourse genera and heterogeneity marks that reveal that, by means of discourse, it was possible to create and determine the decree that imposed sustainability as requisite for Brazilian public universities in a veiled manner, by means of the discourse, which seeks to encompass the character of inference in university autonomy as a pretense demographic consultation of universities (BAKHTIN, 1997; FAIRCLOUGH, 2008; MAGALHÃES, 2001; MAINGUENEAU, 1997; MARCUSCHI, 2007). With these results, we invite the researchers from Organizational Studies to recognize the potential of ACD contribution for understanding the processes of organizational change, as well as highlight the importance that the universities critically reflect over the adoption of requisites such as sustainability.